The Impact of Firm Life Cycle on the Relationship between Financial Reporting Quality and Investment Efficiency: An Empirical Study on Listed Companies in the Saudi Stock Exchange (International Journal of Financial, Administrative and Economic Sciences, 2025)
The research aimed to test the relationship between financial reporting quality and investment efficiency, as well as the moderating effect of stages of the firm's life cycle on this relationship, using a sample of (90) non-financial companies listed on the Saudi Stock Exchange over a period of four years (2020-2023). To achieve this goal, the deductive and inductive approach was used, and multiple linear regression analysis was used to test the research hypotheses. The research found that there is a significant positive effect of financial reporting quality on investment efficiency, and that this positive effect increases in companies going through the growth stage compared to companies in other stages of the life cycle, which include the maturity and decline stages. A set of additional analyses was also conducted to test the robustness of the research results, and the results of these tests show a significant positive effect of the financial reporting quality on investment efficiency in the sample of companies, whether they suffer from overinvestment or those suffering from underinvestment, which is consistent with what was reached in the basic analysis. As for the effect of the stages of the firm's life cycle on the relationship between the financial reporting quality and investment efficiency, the research found that the positive effect of the financial reporting quality on investment efficiency increases in companies that are in the growth stage only in companies that suffer from a lack of investment compared to companies in other stages of the life cycle, which include the maturity and decline stages, which is consistent with what was reached in the basic analysis.
Keywords: Financial Reporting Quality; Investment Efficiency; Firm Life Cycle